2020
DOI: 10.3389/fonc.2020.00995
|View full text |Cite|
|
Sign up to set email alerts
|

Anlotinib Combined With Chemoradiotherapy Exhibits Significant Therapeutic Efficacy in Esophageal Squamous Cell Carcinoma

Abstract: The aim of this study was to evaluate the safety and efficacy of anlotinib combined with chemoradiotherapy for treating esophageal squamous cell carcinoma (ESCC) using patient-derived xenografts (PDXs). Methods: PDX-bearing mice were randomly divided into five groups, as follows: control group receiving normal saline, the group receiving radiotherapy, the group receiving cisplatin combined with radiotherapy, the group receiving anlotinib combined with radiotherapy, and the group receiving anlotinib, and cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Preclinical studies showed that anlotinib and cytotoxic chemotherapy may lead to a synergistic effect, suggesting these drugs may reduce chemotherapy resistance. 13 Considering the modest efficacy and mild toxicity of anlotinib and liposomal doxorubicin for advanced STS, a cohort of patients with advanced STS were treated with anlotinib combined with liposomal doxorubicin followed anlotinib maintenance for survival benefits in three hospitals since 2019. In this study, it aimed to assess the efficacy and safety of anlotinib combined with liposomal doxorubicin followed by anlotinib maintenance monotherapy in patients with metastatic STS.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies showed that anlotinib and cytotoxic chemotherapy may lead to a synergistic effect, suggesting these drugs may reduce chemotherapy resistance. 13 Considering the modest efficacy and mild toxicity of anlotinib and liposomal doxorubicin for advanced STS, a cohort of patients with advanced STS were treated with anlotinib combined with liposomal doxorubicin followed anlotinib maintenance for survival benefits in three hospitals since 2019. In this study, it aimed to assess the efficacy and safety of anlotinib combined with liposomal doxorubicin followed by anlotinib maintenance monotherapy in patients with metastatic STS.…”
Section: Introductionmentioning
confidence: 99%
“…In another clinical trail, it has been noticed that combined administration of nivolumab and Anlotinib as a second-line therapy could improve the physical condition of the patient with advanced ESCC [20]. In addition to that, a recent report has highlighted that anlotinib and chemoradiotherapy in combination has the ideal an-tumor effect to treat ESCC in mice [10]. Not only limited to EC, treatment of Anlotinib works actively in other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Anlotinib has great therapeutic e cacy in treating cancers, such as advanced non-small cell lung cancer (NSCLC), advanced soft tissue sarcoma and metastatic renal cell carcinoma [9]. In ESCC, it has been reported that Antutinib combined with radiotherapy and chemotherapy has strong anti-tumor effects on patient-derived xenografts bearing mice [10]. In a clinical trail, it has been found that Antutinib combined with chemotherapy could improve the survival of patients with advanced ESCC [11], while Antutinib's treatment mechanism for ES still needs further study.…”
Section: Introductionmentioning
confidence: 99%
“…Arotinib have received its rst approval as a thirdline treatment for refractory advanced non-small-cell lung cancer (NSCLC) in May 2018 [14]. Recent studies have demonstrated that anlotinib increases the sensitivity of pulmonary blastoma to chemotherapy in vivo [15]. As we know, activation of the FGFR signaling pathway promotes chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%